Blue Financial Services Group : the perils of rapid expansion - Metton, Eulalie; Mosala, Thabo ([London] : SAGE, 2016)
It was June 2010 and Dave van Niekerk, the CEO of micro-lending company Blue Financial Services (BFS), had just handed in his resignation. BFS, which listed on the Johannesburg Stock Exchange AltX in 2006, had in less than four years expanded its operations to 15 African countries from an original five and employed more than 3000 people. During this time, however, the company had faced escalating problems that had resulted in a write-off of more than R1 billion and a share price - which had reached a high of 700 cents - dropping to 15 cents. This case study discusses this topic.
Originally Published in: Metton, E., & Mosala, T. (2013). Blue Financial Services Group: The Perils of Rapid Expansion. WBS-2013-21. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Financial services industry -- Case studies; Corporations -- Growth -- Case studies